PENGARUH PENDIDIKAN KESEHATAN METODE DISKUSI KELOMPOK TERHADAP PENINGKATAN SKOR PENGETAHUAN LANSIA TENTANG REUMATIK DI POSYANDU LANSIA RW V LEDUG KECAMATAN KEMBARAN BANYUMAS - Atun Raudotul Ma’rifah (Viva Medika, 2013)
Elderly are group vulnerable to disease because of the degenerative process. Disease that often arise in elderly is rheumatism. This can be caused by less of knowledge aboutrheumatic. Less knowledge can be affected by experience, education level, beliefs, facilities,income, and social culture. In increase knowledge about health is a necessary part ofhealth education. Selection methods of health education is important because it can effectthe delivery of information to health education target. The purpose of this study todetermine the effect of health education group discussion method to the elderly scoreagainst increased knowledge about rheumatic. The research was conducted in elderly IHCof RW V Ledug subdistrict Kembaran. The research method used is pre-experimentresearch with the type of one group pretest and posttest design. The population in this wereresearch that the all elderly in IHC of RW V Ledug, while the sample were of 27respondent. Data were collected before and after the health education group discussionmethod using a measuring ratio scale. The result of this study is that there is significant increase of knowledge therespondents before and after health education about rheumatic group discussion methodwith P < 0,01. Key words : Health Education, Knowledge and Rheumatic.